Downregulation of HBx Restrains Proliferation, Migration, and Invasion of HepG2 Cells. (15th May 2021) - Huang, Chaoqun; Liu, Wei; Zhao, Xiaochuan; Zhao, Libin; Wang, Fuxiang
Abstract : Liver cancer is a major contributor to cancer-related death with poor survival for sufferers. Meanwhile, Hepatic B virus X protein (HBx) and XB130 are likely to participate in the pathogenesis of liver cancer. However, the detailed mechanism of HBx/XB130 in liver cancer remains to be further investigated. Our study explored the effects of HBx/XB130 on liver cancer progression. HBx and XB130 expression was detected by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blot. Overexpression of HBx and XB130 was found in liver cancer tissues and cells. Mechanistic study revealed that HBx could bind to and positively regulate XB130 in HepG2 cells. Subsequently, HBx expression was knocked down, while XB130 was overexpressed in HepG2 cells in order to observe the specific role of HBx/XB130 in liver cancer in vitro. Results of CCK-8, Transwell, wound healing, and colony formation assays suggested that HBx could mediate biological function of HepG2 cells by activating the XB130-mediated PI3K/AKT pathway. In summary, our data illustrate that inhibition of HBx effectively suppressed proliferation and metastasis and induced apoptosis of liver cancer cells, which might be partially reversed by XB130. HBx and XB130 may be potential targets for liver cancer pathogenesis.